Low-Cost Embedded System Design for Smart Home Automation Using RF Technology - Yavuz, Erdem (Sciendo, 2024)
Applications for smart home technologies can be described as the adaptation of control systems used in industrial areas to modern living environment of people. Home automation systems are the systematic and seamless adaptation of smart home technologies to the individual's personal needs and desires. Smart homes encompass a range of technologies designed to cater to the needs of residents, simplifying their daily routines and contributing to a more comfortable and secure way of life. Nowadays, most buildings are constructed with expensive, builtin smart home technology. However, when it comes to old buildings without smart home technology, integrating this technology into those structures can be challenging due to the requirement for intrusive overhead wall modifications necessary for installing the technological infrastructure. In this study, a radio frequency based low-cost embedded system is designed to bring intelligent technology to existing homes or old buildings. Various sub-units have been designed and established to be situated in different places of the house. Physical events and situations that occur in the house are sensed by the sub-units and transmitted to the main control unit by means of a specially developed communication protocol via radio frequency signals. This removes the cable clutter and creates a more flexible and easy installation environment.
Keywords: Embedded system; microcontroller; radio frequency; smart home automation